Functional Genomics in Caenorhabditis elegans: An Approach Involving Comparisons of Sequences from Related Nematodes - Thacker, Colin (Cold Spring Harbor Laboratory Press, 1999)
Comparative genomic analysis was used to investigate the gene structure of the bli-4 locus from two related Caenorhabditis species, C. elegans and C. briggsae. In C. elegans, bli-4 is a complex gene encoding a member of the kex2/subtilisin-like family of proprotein convertases. Genomic sequence comparisons coupled with RT–PCR analysis identified five additional coding exons that had not been identified previously using standard recombinant DNA techniques. The C. briggsae gene was able to rescue both viable blistered and developmentally arrested mutants of C. elegans bli-4, demonstrating functional conservation. In addition, deletion analysis of conserved sequences outside of coding regions, combined with phenotypic rescue experiments, identified regulatory elements that alter the expression of the bli-4 gene. These results demonstrate the utility of genomic sequence comparisons of homologous genes in related species as an effective tool with which to dissect the functional information of complex genes. [The sequence for cosmid K0410 is available at GenBank (accession no. AFO 39719); fosmids G06P23 and G25K01 are available as online supplementary material at www.genome.org.]